2011
DOI: 10.1021/nn202860s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Highly Fluorescent Metal (Ag, Au, Pt, and Cu) Nanoclusters by Electrostatically Induced Reversible Phase Transfer

Abstract: This paper reports a simple and scalable method for the synthesis of highly fluorescent Ag, Au, Pt, and Cu nanoclusters (NCs) based on a mild etching environment made possible by phase transfer via electrostatic interactions. Using Ag as a model metal, a simple and fast (total synthesis time < 3 h) phase transfer cycle (aqueous → organic (2 h incubation) → aqueous) has been developed to process originally polydisperse, nonfluorescent, and unstable Ag NCs into monodisperse, highly fluorescent, and extremely sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
314
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 367 publications
(320 citation statements)
references
References 50 publications
5
314
0
1
Order By: Relevance
“…In the present study, the Cu 2p 3=2 band is observed at 932.3 eV (see Fig. S2), which is assigned to Cu(0), 41 and a weak peak can be observed at 942 eV, suggesting very minimal presence of Cu(II) in the system. 42 It is also worth mentioning that the binding energy di®erence between Cu(0) and Cu(I) is only $0.1 eV.…”
Section: Resultssupporting
confidence: 50%
“…In the present study, the Cu 2p 3=2 band is observed at 932.3 eV (see Fig. S2), which is assigned to Cu(0), 41 and a weak peak can be observed at 942 eV, suggesting very minimal presence of Cu(II) in the system. 42 It is also worth mentioning that the binding energy di®erence between Cu(0) and Cu(I) is only $0.1 eV.…”
Section: Resultssupporting
confidence: 50%
“…Cysteine might be essential in cluster formation due to the electron withdrawing effect of the thiol-gold bond, which plays a crucial role in cluster stabilization [44]. If CCWE 6 R 3 was used as a reactant, addition of 1 molar equivalent of free tyrosine or MMYE 6 (Ac-Cys)]-GnRH-I, and their disulfide dimers indicated that the position of Cys residues is a crucial factor in AuQC production. There was no difference in cluster formation using acetylated or nonacetylated versions of GnRH-I derivatives.…”
Section: Preparation Of Auqcs With Peptidesmentioning
confidence: 99%
“…A main strategy for preparation is a top-down approach in which gold clusters are prepared by controlled etching of monolayer-protected gold nanoparticles [5][6][7][8]. A ligand exchange-based reaction has also been reported [9].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the atomically precise composition and determined atom packing structure, thiolate‐stabilized metal nanoclusters have become an ideal system for studying the structure and size‐dependent properties of metal particles. Similarly, these systems have shown some very interesting quantum size effect and core size‐dependent optical and electronic properties 2. Among those studied, most research has been focused on thiol‐stabilized gold and silver nanoclusters (sometimes referred to as monolayer protected nanoclusters).…”
Section: Introductionmentioning
confidence: 99%